"I'm a woman hear me roar!" tattooing and lesbianism as means of communicating feminism and the society's perceptions of such communication tools : a multi-method study - Bautista, Rachelle Penilla 1978-; Juatco, Paulene Iva C.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
Lesbianism, as a movement, is a worldwide phenomenon. It has emerged upon the failure of the women's liberation movement to dissolve inequalities, oppression and subordination experienced by women. It still is a misunterstood issue even in the realm of women's movements and what has been historically entrenched and spread are the biases and misconceptions on lesbians. There is only a handful of inquiries focusing on Filipino sexuality, particularly lesbianism, since Filipinos themselves have their biases or homosexuals in general. The primary reason could be the fact that Filipinos, who are mostly Christians, are still bound by conservative standards of the society within which lesbians and homosexuals are considered immoral. Tattoos as body art have become popular nowadays. Celebrities, elite, yuppies, partygoers, men, women, let a part or even their entire body to be tattooed. Tattooing as an art form could trace its roots to the ancient Japanese culture and throughout history, tattoos have been defined and interpreted in many ways. From being status symbols of the elite, symbol of valor for the warriors, a criminal mark, it is now a "fad" mostly worn by the young people. The researchers, both interested in feminist philosophies, aim to identify and examine the reasons why today's women have their bodies tattooed or become lesbians. In their search for related studies about women sporting tattoos and lesbians, and linking them together with feminism, the researchers have not found any study with the same subject of inquiry. Only a few studies have been done about tattooed women and lesbians separately. This study's goal is to bring light on the ways in which tattoos and lesbianism are used by women to forward their feminist ideals. It is with the hope that this study will gradually eliminate these incorrect stereotyped images of tattooed women and lesbians, and help find effective communication strategies for feminists as they forward their ideals. The general objectives of this study are: (1) to identify up to what extent tattoos and lesbians are used as means of communication feminism, and; (2) to determine the images projected by tattooed women and lesbians, and the society's perceptions of why women convey such images. The researchers used books, theses, articles and websites for the study's related literature. Using the undergraduate thesis "A Descriptive Study on the Image of a Filipino Working Mother" by Josefina Azada, the researchers were able to obtain helpful strategies on how to conduct a study on stereotypes. "The Feminist Poiint of View" by Rosemarie Francisco and "Portrayal of Feminism in US and Filipino Women's Magazines" by Lisa Ann Boquiren served as guidelines for this study. They have provided the researchers a history on the beginnings of feminism in the Philippines as well as the difference of the feminist movements in the US and the Philippines. William Craig Taylor's research in his website on tattoos and their history gave the researchers ideas on how tattoos evolved as an art form. Dulce Anacion's study entitles "Yunal : The Orasyon Tattoo as Folk Literature and Art in Leyte," granted a clear picture on the tattoo practices in the Philippines, particularly in the Leyte-Samar region. The thesis "A Descriptive Study on Lesbianism as the Third Sexual Dimension and its Social Acceptance" by Stephanie Erana provided the researchers a view of the status of lesbians in today's society. The first academic exploration on Filipino lesbians "Sexual Identities and Self Images of Woman-Loving-Women" by Jennifer Curry Josef gave a profile on the stream of thoughts of Filipino lesbians, their private life, and the way they view and identify themselves. Two theories were used for this study: Liberal Feminism and Attribution Theory. Liberal feminism, according to Stephen Littlejohn in his book "Theories of Human Communication, 5th ed.," centers on the idea that women until now do not have the same equal rights with men and that as a sector of the society, women have been abused and oppressed. The Attribution theory, designed by Fritz Heider, works on the processes people hypothesize on the reasons why others behave the way they do. The researchers formulated a theoretical framework model which is an integration of the two theories used for the study. The study used a multi-method approach: focus interview and survey. The respondents for the focus interviews were tattooed women and lesbians who belonged to the 21-35 age bracket. Sample population for the survey came from students of UP Diliman. The focus interview guide was sub-divided into a) Set of Beliefs, b) Knowledge and Awareness, and c) Beliefs and Attitudes. Data were analyzed using frequency distribution and univariate analysis for the quantitative data, while the qualitative data were analyzed using topical thematic analysis. The study was conducted in UP Diliman during the first semester of AY 2000-2001. The common perceptions of people regarding lesbians are individualistic/nonconformist, liberated and rebellious. The perceived reason why women become lesbians is plain preference. Tattooed women are perceived to be liberated, individualistic/nonconformist, and attention-seekers and that, women wear tattoos as self-expression. A big majority of survey respondents believe that a patriarchal society could not fully accept lesbians but could fully accept tattooed women. Generally, the beliefs and attitudes of the respondents towards lesbians were more positive that that towards tattooed women. As for the qualitative findings, lesbian informants view lesbianism as a twofold struggle as it is a struggle not only for lesbian rights but also women's rights. All of them consider lesbianism as a way of communicating feminism. The informants believe that women are still oppressed in society. Consequently, the society's common perceptions towards them made them stronger in asserting their sexual identity and thus moved them to work for better awareness of the society about lesbians in general. The tattooed women informants consider themselves feminists and believe that tattooing, aside from being an art form and self-expression, is also a way of expressing feminism. The survey respondents have gained a better understanding about lesbians and tattooed women by conversing with them. The researchers recommend a study on the extent to which people's attributions to others' behavior they consider deviant are affected by conversations with such people. The researchers also recommend a study linking lesbianism and tattooing with radical feminism--a relatively new form of feminism--since the study solely used the liberal feminist theory. The researchers believe that they have broken some grounds in research since it is the first study to link subcultures, such as tattooed women and lesbians that are considered deviant, to feminism. For the study to be more conclusive of the beliefs and opinions of lesbians in general, focus interviews of lesbians who do not belong in any lesbian organization is recommended. The increasing number of lesbians "coming-out" and women wearing permanent tattoos imply that women now are more vocal and expressive of what they prefer and believe in. Lesbianism is slowly becoming a political stand and is no longer just a sexual preference. Women with tattoos are now seen as artistic. This implies that the contemporary society is more open to accept foreign influences or fads such as tattoos. The researchers recommend an inquiry on effective ways of information dissemination in promoting the right awareness of the society regarding tattooed women, lesbians and women in general. It is further recommended that studies on how to strengthen familial ties and Filipino values be recommended since topics such as lesbianism and tattooing are more likely to be discussed with friends and in school than with family members.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Gay and lesbian studies -- Philippines; Tattooed women -- Philippines; Bisexual feminism -- Philippines